Six Months vs. 12 Months of Adjuvant Trastuzumab Among Women With HER2-Positive Early-Stage Breast Cancer: A Meta-Analysis of Randomized Controlled Trials - Deng, Huan; Du, Xianghui; Wang, Li; Chen, Ming (Frontiers in Oncology, 2020)
Purpose: Both 12 and 6 months of trastuzumab in combination with chemotherapy are effective for HER2+ early-stage breast cancer. This meta-analysis was performed to assess the effectiveness and the toxicity of the two durations. Methods and Materials: We acquired relevant randomized controlled trials (RCTs) from PubMed, the Cochrane Library, ScienceDirect, EMBASE, Ovid MEDLINE, Web of Science, Scopus, and Google Scholar. Our endpoints included disease-free survival (DFS), overall survival (OS), number of recurrences, mortality and early stopping of trastuzumab, and adverse events (AEs). Results: We included five good-quality studies. Both durations of trastuzumab were effective among women with HER2+ early-stage breast cancer, but 12 months of trastuzumab appeared to have better DFS [hazard ratio (HR) = 1.10, 95% confidence interval (CI): 0.99–1.23, P = 0.09] and better OS than 6 months of trastuzumab (HR = 1.14, 95% CI: 0.99–1.32, P = 0.07). However, the 12 month group had more AEs, especially cardiac events [risk ratio (RR) = 0.66, 95% CI: 0.56–0.77, P < 0.00001]. In our sub-analyses, the 12 months duration had better DFS among patients using trastuzumab concurrently than the 6 months duration (HR = 1.23, 95% CI: 1.06–1.44, P = 0.006). Additionally, the 12 months duration had superior OS in women with ER-negative breast cancer (HR = 1.51, 95% CI: 1.10–2.08, P = 0.01) and patients treated with trastuzumab concurrently than the 6 months duration (HR = 1.61, 95% CI: 1.13–2.29, P = 0.008). Conclusions: Twelve months was the standard duration of adjuvant trastuzumab among patients with HER2+ early-stage breast cancer, with a tendency toward superior survival. However, patients in the 12 month group had more significant cardiac toxicity than those in the 6 month group.